Time-Lapse Video Microscopy of Gliding Motility in Toxoplasma gondii Reveals a Novel, Biphasic Mechanism of Cell Locomotion - Håkansson, Sebastian (The American Society for Cell Biology, 1999)
Toxoplasma gondii is a member of the phylum Apicomplexa, a diverse group of intracellular parasites that share a unique form of gliding motility. Gliding is substrate dependent and occurs without apparent changes in cell shape and in the absence of traditional locomotory organelles. Here, we demonstrate that gliding is characterized by three distinct forms of motility: circular gliding, upright twirling, and helical rotation. Circular gliding commences while the crescent-shaped parasite lies on its right side, from where it moves in a counterclockwise manner at a rate of ∼1.5 μm/s. Twirling occurs when the parasite rights itself vertically, remaining attached to the substrate by its posterior end and spinning clockwise. Helical gliding is similar to twirling except that it occurs while the parasite is positioned horizontally, resulting in forward movement that follows the path of a corkscrew. The parasite begins lying on its left side (where the convex side is defined as dorsal) and initiates a clockwise revolution along the long axis of the crescent-shaped body. Time-lapse video analyses indicated that helical gliding is a biphasic process. During the first 180(o) of the turn, the parasite moves forward one body length at a rate of ∼1–3 μm/s. In the second phase, the parasite flips onto its left side, in the process undergoing little net forward motion. All three forms of motility were disrupted by inhibitors of actin filaments (cytochalasin D) and myosin ATPase (butanedione monoxime), indicating that they rely on an actinomyosin motor in the parasite. Gliding motility likely provides the force for active penetration of the host cell and may participate in dissemination within the host and thus is of both fundamental and practical interest.